f(-a) is the remainder when f(x) is divided by (x+a). This can be obtained by remainder theorem for polynomials.
Given that f(x) is divided by (x+a) and leaves a reminder
Using the remainder theorem for polynomials we get,
f(x) = (x+a)·g(x) + r, where g(x) is the quotient and r is the remainder.
Put x = -a, then
f(-a) = (-a+a)·g(-a) + r
f(-a) = (0)·g(x) + r
f(-a) = r
f(-a) is the remainder.
Hence f(-a) is the remainder when f(x) is divided by (x+a).
Learn more about remainder theorem here:
brainly.com/question/1550437
#SPJ4